Postcolonial Feminism and Intersectionality: A Comparative Study of Gender, Race, And Identity in Contemporary Literary Criticism (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of this study is to investigate the complex relationship between gender, race, and identity in contemporary literary criticism by examining how postcolonial feminism and intersectionality represent these three aspects of the literary world. Within the scope of this research, a wide range of postcolonial literature is analyzed in order to demonstrate how cultural contexts, gender roles, and racial identities all collaborate to bring about changes in colonial power structures. It is through the investigation of the ways in which gender, class, and race interact to define the lives of characters and their defiance to patriarchal and imperialist ideals that the study sheds light on the relevance of intersectionality. finding similarities between works from Africa, South Asia, and the Caribbean, this research use a comparative methodology to explain how marginalized identities in postcolonial settings encounter both universal and context-specific difficulties. This is accomplished by finding parallels between the works of these three regions. By showing the continued significance of postcolonial feminist ideas in contemporary literary discourses, this research makes a contribution to the ongoing conversations that are taking place about gender equality, intersectionality, and identity politics.